Effect of age and type of reinforcer in the equivalence – equivalence by a partition procedure - Andres Garcia (Universidad de San Buenaventura, 2011)
Equivalence – Equivalence responding (Barnes et al., 1997), based on derived or non-explicitly trained relational responding, supports a behaviour-analytic model of analogical reasoning. Conditional discriminations are the most common procedure used to train its prerequisites. In this exploratory work we test Vaughan’s (1988) simple discrimination procedure instead to derive Eq-Eq responses in children. Two factors were assessed: type of reinforcer used (primary or secondary) and age of participants (9-10 or 12-13 years). The procedure successfully leaded to the derivation of equivalence – equivalence responses, and both factors influenced the results: selecting older children and applying primary reinforcement leaded to faster learning and better results in the equivalence – equivalence test. No interaction between factors was found. This training procedure can provide a new way to investigate the behavioural prerequisites of this important ability